2020
DOI: 10.1002/ange.202001065
|View full text |Cite
|
Sign up to set email alerts
|

Water Catalysis of the Reaction of Methanol with OH Radical in the Atmosphere is Negligible

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…The impact of water molecules on the CH 3 OH + OH reaction was investigated by Chao et al, 55 who reported a negligible catalytic effect at atmospheric pressure and room temperature. The result was later corroborated by theoretical calculations made by Wu et al 56 We assume that this conclusion is valid also for high-pressure and high-temperature conditions.…”
Section: Ch 3 Oh + Oh Reaction (R2 and R3supporting
confidence: 82%
“…The impact of water molecules on the CH 3 OH + OH reaction was investigated by Chao et al, 55 who reported a negligible catalytic effect at atmospheric pressure and room temperature. The result was later corroborated by theoretical calculations made by Wu et al 56 We assume that this conclusion is valid also for high-pressure and high-temperature conditions.…”
Section: Ch 3 Oh + Oh Reaction (R2 and R3supporting
confidence: 82%
“…In the aqueous environment, water clusters with different sizes and conformations have a great probability of participating in the reaction. The processes for the formation of NH 3 + OH + (H 2 O) n → NH 2 + H 2 O + (H 2 O) n are divided into three main steps: 22,37,38 where A represents the reactant NH 3 or OH, B represents (H 2 O) n ( n = 1–3), C represents a bimolecular complex, and k 1 and k −1 are the forward and reverse rate constants, respectively, in step a. D represents another reactant, E represents the precursor complex, and k 2 and k −2 are the corresponding forward and reverse rate constants, respectively, in step b.…”
Section: Calculational Methodsmentioning
confidence: 99%
“…In the aqueous environment, water clusters with different sizes and conformations have a great probability of participating in the reaction. The processes for the formation of NH 3 + OH + (H 2 O) n / NH 2 + H 2 O + (H 2 O) n are divided into three main steps: 22,37,38 Step a…”
Section: Calculational Methodsmentioning
confidence: 99%
“…Additionally, the hydroxyl radical is the main oxidizer in both daytime atmospheric and combustion processes, so the reaction with methanol provides a sink for this simple alcohol. Owing to the importance of these species in various environments, many kinetic , and theoretical studies have been carried out over a range of temperatures and pressures. The negative temperature dependence of the total reaction rate at low temperatures has led to many investigations that highlight the significant role the prereactive complex has in the kinetics of this reaction by facilitating tunnelling through the H-abstraction barrier to CH 3 O products at low temperatures.…”
mentioning
confidence: 99%
“…The negative temperature dependence of the total reaction rate at low temperatures has led to many investigations that highlight the significant role the prereactive complex has in the kinetics of this reaction by facilitating tunnelling through the H-abstraction barrier to CH 3 O products at low temperatures. This result has motivated numerous studies ,,, with significant implications toward bimolecular cold chemistry occurring in the ISM, which has previously been overlooked as a source for complex organic molecules. ,, …”
mentioning
confidence: 99%